Determinasi Financial Planning dan Financial Stress terhadap Perilaku Peminjaman Ulang di Kalangan Generasi Muda Pengguna P2P Lending: Perspektif Psikologi Keuangan - Abdiel Reihan; Ratri Kurniasari; Iis Mariam (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study investigates how financial planning and financial stress influence repeated borrowing behaviour among young users of Peer-to-Peer (P2P) lending platforms through a psychological finance perspective. The research aims to measure the impact of individual financial planning and perceived financial stress on continuance intention to borrow among borrowers aged 19–34 in Depok. Data were collected through a cross-sectional survey of 100 purposively selected active P2P borrowers, using multi-item Likert scales to assess each construct. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to examine both measurement and structural models. The results demonstrated satisfactory reliability and validity (AVE > 0.50; composite reliability > 0.90) with substantial explanatory power (R² = 0.659). Financial planning exhibited a negative effect (β = −0.416, p < 0.001), while financial stress showed a positive effect (β = 0.470, p < 0.001) on continuance intention to borrow. These findings highlight the dual psychological mechanisms of rational control and emotional pressure driving repeated borrowing, suggesting the need for financial education and stress-coping programs within P2P lending ecosystems.